Revitalizing the Pancasila Ideology in the Global Level of the Rule of Law Perspective - Hidayat, Arief (Law Research Review Quarterly, 2016)
GLOBALIZATION is a fact. It can no longer be avoided. Both positive and negative effects of globalization must be addressed and responded to appropriately. The Indonesian people are demanded not to be passive about the current of globalization. Globalization is the challenge of the times. With regard to democracy, globalization breeds its own paradox: on the one hand the globalization of democracy results in the bankruptcy of many ideologies, on the other it also encourages the rise of local nationalism, even in its most shallow and narrow forms such as ethnonationalism, or even tribalism.